Graphene: A Rising Star on the Horizon of Materials Science - Ujjal Kumar Sur (International Journal of Electrochemistry)
Graphene, a one-atom thick planar sheet of sp2 bonded carbon atoms packed in a honeycomb lattice, is considered to be the mother of all graphitic materials like fullerenes, carbon nanotubes, and graphite. Graphene has created tremendous interest to both physicists and chemists due to its various fascinating properties, both observed and predicted with possible potential applications in nanoelectronics, supercapacitors, solar cells, batteries, flexible displays, hydrogen storage, and sensors. In this paper, a brief overview on various aspects of graphene such as synthesis, functionalization, self-assembly, and some of its amazing properties along with its various applications ranging from sensors to energy storage devices had been illustrated.